Exploring the Relations Between Religious Orientation and Racial Identity Attitudes in African College Students: A Preliminary Analysis. (May 2016) - Sanchez, Delida; Gilbert, Dorie J.
As the Black African college student population increases across U.S. college campuses, helping professionals are encouraged to more clearly understand the unique identity developmental needs of these students in order to fortify their academic endeavors and contribute to their success. Both religion and race are powerful forces that shape identity, providing an overall sense of purpose, a feeling of connection with others, and a sense of community. Yet, both of these aspects of identity are rarely studied in Black African college student populations. This study examined the relations between religious orientation and racial identity attitudes in 49 Black African college students, whose diverse racial, ethnic, and religious experiences have been understudied. The results from multiple regression analyses indicated that religious orientation was significantly related to racial identity status. Specifically, intrinsic religious orientation was positively related to preencounter (i.e., pro-White, anti-Black beliefs about one's own racial group) racial identity attitudes, quest religious orientation was positively related to immersion-emersion (i.e., anti-White, pro-Black attitudes about one's own racial-cultural group) racial identity attitudes, and the relations between intrinsic religious orientation and internalization (i.e., internalized positive self-acceptance) racial identity attitudes approached significance. Recommendations for future research and implications for diversity in higher education are discussed.